Transition of care : from childhood to adulthood in endocrinology, gynecology, and diabetes - Polak, Michel; Touraine, Philippe (Basel : Karger, 2018)
Pediatricians face many questions and challenges during patients' transition from childhood to adulthood. Chronic diseases justify long-term medical, psychological, educational, and social management. The establishment of networks with adult endocrinologists is, therefore, very important to achieving optimal conditions for a successful transition period. In this book, leading experts discuss major public health issues such as diabetes and obesity. They also review genetic diseases, including Turner syndrome and congenital adrenal hyperplasia. All clinical cases are presented in a focused way to highlight any issues which might be discussed by the doctor with patients and family. Psychological approaches are debated as are proposals for defining specific tools to encourage autonomy during this life period. This book is a valuable tool and will be helpful in answering many questions for endocrinologists, adult and pediatric, dedicated to the long-term management of patients with chronic diseases.
Keywords: ENFERMEDADES CRÓNICAS; TRANSICIÓN A LA ATENCIÓN DE ADULTOS; ENFERMOS CRÓNICOS -- ATENCIÓN MEDICA; ENFERMEDADES CRÓNICAS -- TRATAMIENTO